PERLINDUNGAN HUKUM BAGI PEMEGANG SAHAM MINORITAS DALAM PERUSAHAAN PERSEROAN - Rafi Akbar Al Aqib; Azi Fachri Mandala; Jhames Jorgi (Media Keadilan: Jurnal Ilmu Hukum, 2023)
The causes of weak shareholder protection include a lack of awareness of how corporate governance is implemented by public companies, to the opportunistic behavior of public companies that use loopholes in regulations and weaknesses in capital market law enforcement. Because they play a dominant role in the area of capital market regulation, capital market regulatory bodies have been widely criticized in response to takeovers of minority shareholders. The purpose of this study is to examine cases of legal protection for minority shareholders in order to gain an understanding not only of the legal issues and challenges that exist in implementing regulations in the field of shareholder protection but also to recommend possible ways to improve law enforcement in order to ensure the effectiveness of shareholder protection in Indonesia. The research method used is normative juridical research method. Every shareholder who is harmed by the company's actions as a result of the decision of the GMS, Directors, and/or Commissioners has the right to submit a complaint to Article 61 UUPT. Based on the financial transaction case of PT Sumalindo Tbk which discriminates against minorities caused by legal loopholes and weak capital market law enforcement. Also, OJK needs to give priority to taking a risk-based approach that is far more total and systematic than existing regulations. An alternative measure to increase awareness of Indonesian public companies is good corporate governance by introducing a mechanism that assesses the performance of companies based on their compliance with corporate governance norms.